Growth and Colonization in Eucalyptus tereticornis (Hybrid) Seedlings Inoculated with Different Inoculum formulations of Pisolithus tinctorius - Badshah, N. K. Umar; Naik, S. T. (Indian Forester, 2006)
In the present investigation, efforts are made to use Pisolithus tinctorius as both seed and soil inoculum to know their efficacy. In seed inoculation experiment, spores and pure culture of P. tinctorius showed highest emergence, survival, colonization of seedling and resisted the disease incidence by Cylidrocladium scoparium the causal organism for seedling blight. In soil inoculation experiment, the treatment with P. tinctorius pure culture recorded significantly higher height (90.07 cm), collar diameter (0.49 cm), root length (42.08 cm) and dry biomass (7.26 g) over pathogen and control treatments. Regarding the efficacy of P. tinctorius against Cylidrocladium scoparium, it was found that the treated seedlings with extomycorrrhizal culture exhibited lowest disease incidence (31.15%) and mortality (8.62%) of seedlings. The maximum phosphorous content (4.66 mg) was recorded in the seedlings of Eucalyptus hybrid inoculated with P. tinctorius pure culture this was due to higher colonization of roots (61.85%)